Effectiveness Report of T-AYU-HM Premium and Onion Vaporisation on Corona Positive Sickle Cell Anemia Patients: A Case Study (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Corona virus increases mortality in patients with comorbidities like diabetes, hypertension, cancer, haemoglobin disorders. The entry of corona virus in sickle cell anemia patients demands a personalised medical management strategy because till date standard cure is not available for both the illnesses. Coronavirus infection causes damage to alveoli leading to an impaired oxygen exchange which might result in sickling of red blood corpuscles inducing various complications in patients of sickle cell anemia. Management of sickle cell patients infected with coronavirus has presented with a challenge in the current situation. A case report discuss here is of 2 sickle cell anemia patients with positive Covid-19 test who came to the clinic seeking treatment. With prior consent, we advised T-AYU-HM Premium and Onion vaporisation treatment for 21 days. We observed remarkable clinical improvement in patients’ haemoglobin, RBC, ESR and CRP profiles during followed up visit. The formulation’s impact on red blood corpuscles helps in preventing vaso-occlusive crisis and thereby the requirement of hospitalisation. The patients’ clinical recovery observed without any use of supportive medications commonly required in patients of sickle cell and coronavirus infection. This case report study provides information on the role of an alternative system of medicine in comorbidities in patients infected with coronavirus across the country. This therapeutic approach might open a door for an economical, safe and effective management options for sickle cell anemia patients infected with coronavirus in future.